Optimal Pricing and Quality Decisions Under Cooperative Promotion of Cross-Market Service Platforms - Yan, Ke; Hua, Guowei; Cheng, T.C.E.; Choi, Tsan-Ming; Dong, Jing-Xin; Li, Xinzhu (IEEE transactions on engineering management, 2024)
In order to enhance the competitiveness of firms and seek more opportunities, it is increasingly popular for service platforms in different markets to promote their products jointly. To acquire a competitive edge and enhance sustainability of supply chains, it is crucial for such cross-market service platforms to take into account the cost incurred in promotion in addition to the price and quality of their products. We use game-theoretic models to investigate the effects of cooperative promotion on cross-market service platforms' optimal decision making and their supply chains, with a specific focus on whether they should adopt cooperative promotion by offering customers joint membership of the partnering platforms. It has been found that service platforms' choices on cooperative promotion are subject to the extent to which demands are influenced by joint promotional activities, price and quality of platforms. When the independent promotional activities of the service platforms have low impacts on demand, cooperative promotion tends to be more beneficial in terms of increasing the platforms' profits, and a higher demand also makes their respective supply chains more sustainable. Conversely, as the impact of the joint promotional activities on demand changes, lower prices and quality may improve or reduce the platforms' profits, but a lower demand will harm the sustainability of their respective supply chains. In addition, the higher the basic market demands for the service platforms are, the more advantage the service platforms will gain through cooperation and, consequently, they are less willing to invest more in cooperative promotion.